Clustering-Based Analysis of Green Area Reduction and Thermal Impact in Marabá-PA - Ferreira, Mayara; Castro, Vitor; Alves, Marcela; Kuribayashi, Hugo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.11778, 2025)
This study investigates the thermal impact related with the reduction of green areas in the municipality of Marabá-PA through the analysis of satellite imagery and the application of Machine Learning (ML) clustering techniques. The temporal evaluation reveals a significant expansion of urban areas accompanied by a marked decline in vegetated regions. The results demonstrate a strong correlation between decreased green cover and increased land surface temperatures, exacerbating the effects of the local heat island. These findings underscore the urgent need for integrated environmental preservation strategies and the implementation of public policies that promote sustainable urban growth. Recommendations include prioritizing the restoration of green infrastructure, adopting integrated urban planning that respects historical land use patterns, and balancing economic development with the conservation of natural resources to mitigate thermal impacts and improve regional quality of life.